Etiology, staging, and management of cystocele - Sabahath, Sheema; Bogis, Abdullah Haitham; Mutairi, Taif Shabib Al; Alshahabi, Hasan Yousef; Sayhab, Hussain Ahmed Al; Basyouni, Faris Hasan; Shehab, Samah Mohamed; Hijji, Mohammed Khaled Al; Alhusaini, Eilaf Ahmed; Aljohani, Alfaf Salah (International Journal Of Community Medicine And Public Health, 2022)
A cystocele is usually found to protrude the urinary bladder through the vaginal wall. Various causes have been reported in the literature for the pathogenesis and development of cystocele. These can cumulatively lead to a remarkable weakness in the muscular and connective tissue layers related to the urinary bladder and anterior vaginal wall. The present study discusses the etiology, staging, and management of patients with cystocele. Evidence indicates that a defect within the pelvic-floor supporting system can significantly lead to the development of cystocele. Parity, increasing age, and obesity are the main associated risk factors for developing these events. Staging is important to decide the most suitable treatment plan, which might be conservative or surgical. Some patients do not require any management approach, being asymptomatic, and refuse the current treatment modalities. Surgery has been associated with enhanced outcomes and can be conducted via two different approaches, including anterior colporrhaphy and sacral colpopexy.